Determinan Kejadian Tuberkulosis pada Anak Balita di Indonesia: Analisis Data Sekunder dari SSGI 2022 - Wayan Aryawati; Yogi Ari Ghopican; Nova Muhani; Samino Samino; Khoidar Amirus (Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract Tuberculosis (TB) in toddlers remains a serious public health problem in Indonesia, especially among vulnerable groups. This study aims to analyze the determinants of TB incidence in toddlers using secondary data from the 2022 Indonesian Nutritional Status Survey (SSGI) through a cross-sectional design. Of the 334,848 toddlers interviewed in 33 provinces and 486 districts/cities, after data cleaning, a final sample of 42,379 toddlers was obtained. Univariate, bivariate (chi-square), and multivariate (binary logistic regression) analyses showed that only poor nutritional status (p=0.013; OR=1.983) and untimely provision of complementary foods (p=0.049; OR=0.704) were significantly associated with TB incidence. Other variables such as exclusive breastfeeding (p=0.068), access to health services (p=0.129), drinking water sources (p=1.000), and completeness of immunizations (p=0.475) were not significant. Poor nutritional status is the strongest risk factor, almost doubling the likelihood of developing TB. Therefore, improving nutritional status, providing timely complementary foods, promoting exclusive breastfeeding, and increasing coverage of complete basic immunization through promotive and preventive approaches are priority strategies to reduce TB incidence among toddlers in Indonesia. Keywords: Tuberculosis, toddlers, SSGI